Types of code switching found in the twitters of the indonesian kpop fans - Ariasih, Ni Putu Liana; Jendra, I Made Iwan Indrawan; Sulatra, I Komang (Journal of Language and Applied Linguistics, 2021)
This study aims to find out the types of the code switching occur in the tweets posted by the Indonesian K-Pop Fans on Twitter. As the phenomenon of code switching in social media is very common nowadays, it makes the writer interested in doing this research. The fifteen data were collected and analyzed by using descriptive qualitative method. In analyzing data, the writer uses the theory proposed by Poplack (1980). The result of this study shows that from fifteen tweets only two types of code switching were found namely inter-sentential switching and intra-sentential switching.